Differential Microwave Resonator Sensor Reveals Glucose-Dependent Growth Profile of E. coli on Solid Agar - Jain, Mandeep Chhajer; Nadaraja, Anupama Vijaya; Vizcaino, Bianca Marjan; Roberts, Deborah J.; Zarifi, Mohammad H. (IEEE microwave and wireless components letters, 2020)
This letter presents a practical application of a differential microstrip microwave sensor for label-free and real-time monitoring of Escherichia coli ( E. coli ) growth under different nutritional conditions on solid agar media. Two planar microstrip ring resonators coupled with a one-port power divider form the core of the sensing system. The sensing resonator operates at 1.509 GHz with an amplitude of −10.21 dB and the reference resonator operates at 1.798 GHz with an amplitude of −11.75 dB. The growth profile of E. coli at each glucose concentration in Luria-Bertani (LB) agar was derived by measuring the resonant amplitude variations ( Δ A ) and is further supported by microscopic images. A complete inhibition of growth was observed at 10% glucose concentration. This research expands the application of microwave sensors to investigate the effect of nutritional parameters on bacterial growth.